Structure of Fish Communities Results of Fishermen's Catches in The Waters Around Mangroves on The Coast Lembar of West Lombok - Medinah, Deayu Mitha Lailatul; Syukur, Abdul; Ilhamdi, Mohammad Liwa (Biology Education Study Program, Faculty of Teacher Training and Education, University of Mataram, Indonesia, 2024)
Fish have an important role as an ecological and economic function. This research aims to determine the structure of the fish community based on fishermen's catches in the waters around the coastal mangroves of West Lombok. Data collection uses survey and observation methods. Next, data analysis of fish diversity values ​​used the Shannon-Wiener Index (H'), Uniformity Index (E), and Dominance Index (D). The results of this research have found 40 species, consisting of 5,012 individuals in 20 families. Furthermore, the fish species that has the highest number of individuals is Nemipterus Marginatu (0.144%) of the total number of individuals. Meanwhile, the fish species with the lowest number of individuals is Neotygon Kuhlii (0.01%). The value (H') of fish species in landings in the northern part is higher with a value (H') of 2.946, while in landings in the southern part it is 2.839, and the uniformity index (E) of fish in the northern part is 0.074, while landings in the southern part are 0.074. 0.024, Meanwhile the Fish Dominance Index (D) in the northern part is smaller with a value of 0.071 compared to landings in the southern part of 0.084. Conclusion of research on the structure of fish communities in waters around mangroves with the composition of the most Nemipterus Marginatu species and the least Neotygon Kuhlii. The level of fish species diversity is in the medium category with the level of uniformity and dominance also in the medium category.